Advanced glycation end products and their receptors in serum of patients with type 2 diabetes - Diana Indyk (Nature Portfolio, 2021)
Abstract Glycation is a non-enzymatic process involving the reaction of reducing sugars or reactive oxoaldehyde with proteins, lipids or nucleic acids, which results in the formation of advanced glycation end products (AGEs). The presented work discusses the glycation process in people with advanced stage of type 1 or type 2 diabetes. The concentration of different AGEs and their receptors for 58 serum samples was determined by ELISA and by spectrofluorimetric methods. In addition to fluorescent low molecular weight and protein-bound AGEs, we have also marked a new class of AGEs: melibiose-derived glycation product (MAGE). Our attention was also focused on the two groups of AGEs receptors: scavenger receptors (SR-A and SR-B) and RAGE. The correlation between the SR-AI scavenging receptors concentration and the fluorescence of AGEs as well as diabetes biological markers: GFR, creatinine contentration and HbA1c was demonstrated. A relationship between the concentration of AGEs and their receptors was also found in serum sample of patients treated with the metformin and aspirin. Furthermore, the concentration of SR-AI scavenger and the fluorescence of total AGEs was significantly lower in treated patients than in non treated patients. AGEs have also been found to contribute to the development of cardiovascular disease, atherosclerosis and diabetic complications, what could be deduced from the correlation of AGEs level and HDL cholesterol or uric acid level. Thus, it was confirmed that AGEs are involved in the pathomechanism of diabetes and other degenerative diseases. Nowadays, it is believed that AGEs due to the long time remaining in the body may be an important diagnostic marker. Their determination may allow monitoring the progression of the disease and the effectiveness of the therapy.